Major Payoffs: Postcollege Income, Graduate School, and the Choice of "Risky" Undergraduate Majors. (August 2017) - Monaghan, David; Jang, Sou Hyun
Although the bachelor's degree is considered the "great equalizer, " returns vary substantially by field of study, particularly in the years immediately following graduation. In the first section of our analysis, we study the varying labor market experiences of recent graduates with different majors. We build on prior research by more fully accounting for the complicating role of graduate school attendance in the relationship between majors and income. We find some majors to be distinctly "risky, " exposing their holders to heightened risk of low income and unemployment during the postcollege transition. Those who select such majors are much more likely to later enroll in graduate school. After 10 years, graduate degrees mitigate, but do not entirely erase, major-based income disparities. We use these findings in the second section to explore the determinants of major choice among first-time freshmen. Female and higher socioeconomic status (SES) students are more likely to select risky majors, but the latter relationship is entirely explained by academic and institutional variables. In contrast to prior research, we find strong institutional effects on major choice, with those attending selective colleges, smaller institutions, and institutions with fewer low-SES students more likely to select risky and graduate-school-associated majors, net of individual-level factors. We conclude by discussing the implications of our findings for the situation of the arts and sciences fields in the era of mass enrollment.